HIGH-RISK INTRAOCULAR RETINOBLASTOMA: Comparison Between Asian Indians and Americans From Two Major Referral Centers. Issue 10 (October 2018) - Kaliki, Swathi; Shields, Carol L.; Eagle, Ralph C.; Iram, Sadiya; Shields, Jerry A.
Abstract : Purpose: To identify the differences in the clinical and histopathologic features in eyes with advanced intraocular retinoblastoma in a developing country (India) versus a developed country (USA). Methods: Retrospective study. Results: Of 524 patients with retinoblastoma who underwent primary enucleation, 331 were from India, and 193 were from the USA. Asian Indians were older at presentation (35 months vs. 29 months; P = 0.02), had thicker tumors (13.8 mm vs. 12.4 mm; P = 0.0001) compared with Americans. High-risk intraocular retinoblastoma was more common in Asian Indians with a 2-fold greater risk compared with Americans (35% vs. 23%; odds ratio = 1.83; P = 0.003). Statistically significant differences in the histopathologic features (Asian Indians vs. Americans) included massive (≥3 mm) choroidal infiltration (17% vs. 6%; P = 0.0003) and optic nerve infiltration (48% vs. 15%; P = 0.0001). Asian Indians had a 5-fold greater risk of having optic nerve invasion (odds ratio = 5.45; P < 0.0001) and 3-fold greater risk of massive choroidal invasion (odds ratio = 2.80; P < 0.0001) compared with Americans. With appropriate use of adjuvant systemic chemotherapy, the difference in the rates of systemic metastasis (5% vs. 2%, P = 0.67) and related death in both countries (5% vs. 0%, P = 0.14) were not statistically significant. Conclusion: High-risk intraocular retinoblastoma is more common in Asian Indians compared with Americans. Abstract : In this study of two populations who underwent primary enucleation for retinoblastoma, Asian Indians had 5-fold greater risk of having optic nerve invasion (odds ratio = 5.45; P < 0.0001) and 3-fold greater risks of massive choroidal invasion (odds ratio = 2.80; P < 0.0001) compared with Americans.